A New Information Hiding Method for Audio Signals - Avci, Derya; Tuncer, Turker; Avci, Engin (Ieee, 2018)
Transparency, durability and capacity are the performance criteria of data hiding algorithms. In this study, data hiding was performed for the audio data. The most commonly used frequency conversion is Discrete Wavelet Transform (ADD). In this study, high pass filter coefficients were obtained by using ADD. Then the LSB method was applied to these coefficients. The transparency and capacity of the multilevel ADD-LSB method are measured and statistical results are obtained.
6th International Symposium on Digital Forensic and Security (ISDFS) -- MAR 22-25, 2018 -- Antalya, TURKEY
Keywords: Data Hiding; Audio Stegonography; Audio Processing; ADD; Information Security